No Future, No Children? Towards a Re-Complexification of “Eco-Reproductive” Concerns in French-speaking Switzerland - Krähenbühl, Mathilde (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2022)
Although endangered future generations are omnipresent in discourses around climate change, the possibility to opt out of parenthood based on environmental reasons raises ambiguous reactions. Taking up two distinct registers that characterise stereotyped representations of “eco-reproductive” concerns, this article aims to re-complexify how ecologists connect reproduction and environmental crises. Mobilising ethnographic interviews conducted in Lausanne, Switzerland, I analyse how my interlocutors sometimes reproduce or break up with eco-Malthusian arguments. By extension, I explore what it tells us about their political views. Observing that they preconise collective action rather than individual ecological practices, I further interrogate their visions of the future. Producing “counter-Anthropocene” imaginaries more than nourishing a deliberate conviction in “collapse”, I argue that reconsidering parenthood allows them to deal with uncertainty and re-establish anticipation. Pas de futur, pas d’enfants ? Vers une re-complexification des préoccupations « éco-reproductives » en Suisse romande Bien que les menaces qui pèsent sur les générations futures soient omniprésentes dans les discours sur le changement climatique, la possibilité de renoncer à la parentalité pour des raisons écologiques suscite des réactions ambiguës. Reprenant deux registres distincts qui caractérisent les représentations stéréotypées des préoccupations « éco-reproductives », cet article vise à re complexifier la manière dont les écologistes relient reproduction et crises environnementales. Mobilisant des entretiens ethnographiques menés à Lausanne, en Suisse, j’analyse la manière dont mes interlocuteurs et mes interlocutrices reproduisent ou rompent parfois avec les arguments éco-malthusiens. Par extension, j’explore ce que cela nous dit de leurs opinions politiques. Observant qu’ils/elles préconisent l’action collective plutôt que les « écogestes » individuels, j’interroge plus avant leurs visions du futur. Produisant des imaginaires « contreanthropocène » plutôt que de nourrir une conviction délibérée de « l’effondrement », je soutiens que le fait de reconsidérer la parentalité leur permet de faire face à l’incertitude et de rétablir une anticipation.